TEXT DEIXIS IN NARRATIVE SEQUENCES - Rivera, Josep (International Journal of English Studies, 2009)
This study looks at demonstrative descriptions, regarding them as text-deictic procedures which contribute to weave discourse reference. Text deixis is thought of as a metaphorical referential device which maps the ground of utterance onto the text itself. Demonstrative expressions with textual antecedent-triggers, considered as the most important text-deictic units, are identified in a narrative corpus consisting of J. M. Barrie’s Peter Pan and its translation into Catalan. Some linguistic and discourse variables related to DemNPs are analysed to characterise adequately text deixis. It is shown that this referential device is usually combined with abstract nouns, thus categorising and encapsulating (non-nominal) complex discourse entities as nouns, while performing a referential cohesive function by means of the text deixis + general noun type of lexical cohesion.